1998
DOI: 10.1103/physrevlett.81.4580
|View full text |Cite
|
Sign up to set email alerts
|

Sub-barrier Fusion ofH6ewithB

Abstract: The fusion of 6 He with a 209 Bi target has been studied at energies near to and below the Coulomb barrier. Despite the weak binding of the valence neutrons in 6 He, little evidence is found for suppression of fusion due to projectile breakup. Instead, a large enhancement of sub-barrier fusion is observed. It is suggested that this enhancement may arise from coupling to positive Q value neutron transfer channels, resulting in "neutron flow" between the projectile and the target. [S0031-9007 (98)07674-1] PACS n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
276
3
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 281 publications
(307 citation statements)
references
References 20 publications
23
276
3
5
Order By: Relevance
“…4, where the two-neutron evaporation channel of the system 6 He + 208 Pb is compared with the corresponding 4 He + 208 Pb system (both producing the same compound nucleus 212 Pb). Despite the differences observed in the data sets, an overall enhancement of the fusion cross sections is observed when compared to the tightly bound 4 He isotope, in agreement with previous results [10][11][12][13][14]. Fig.…”
Section: Fusion and Reaction Cross Sectionssupporting
confidence: 90%
See 1 more Smart Citation
“…4, where the two-neutron evaporation channel of the system 6 He + 208 Pb is compared with the corresponding 4 He + 208 Pb system (both producing the same compound nucleus 212 Pb). Despite the differences observed in the data sets, an overall enhancement of the fusion cross sections is observed when compared to the tightly bound 4 He isotope, in agreement with previous results [10][11][12][13][14]. Fig.…”
Section: Fusion and Reaction Cross Sectionssupporting
confidence: 90%
“…At the experimental side several measurements of the fusion excitation function of 6 He with heavy targets ( 206 Pb, 209 Bi, 238 U) have been performed at different facilities. After the pioneering work of J.J. Kolata and E.F. Aguilera [10][11][12] using the TWINSOL facility at Notre Dame (USA), additional measurements were carried out by R. Raabe [13,14] and R. Wolski [15] using the CRC facility at Louvain-la-Neuve (Belgium), and by Y.E. Penionzhkevich [16] and S.M.…”
Section: Fusion and Reaction Cross Sectionsmentioning
confidence: 99%
“…A clear and specific example of the relevance of elastic scattering experiments is the discovery of the atomic nucleus in 1911, made by Ernest Rutherford. Lately, many experiments and theoretical analyse have been performed using radioactive beams as projectiles to produce a nuclear reaction [1,2,3,4,5,6,7,8,9,10,11,12,13,14,15,16]. It is well known that in general experiments with halo nuclei are difficult to carry out, mainly because of the low intensities of the respective beams.…”
Section: Introductionmentioning
confidence: 99%
“…This effect can first be investigated using stable weakly bound beams which have much higher intensities than radioactive beams. The suitable stable nuclei for this kind of study are 9 Be, 6 Li and 7 Li with separation energies of 1.57, 1.47 and 2.47 MeV, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Recently a series of experiments have been performed with the aim to study the fusion-fission process using 6 He beams with close-to-barrier energies [3][4][5][9][10][11]. However, the obtained data were rather controversial and showed that higher statistical confidence is necessary as well as more informative experiments giving possibilities of distinguishing different exit reaction channels.…”
Section: Introductionmentioning
confidence: 99%